Predição de extravasamentos devido à infiltração de águas pluviais em interceptor de esgotamento sanitário de Fortaleza/CE - Lopes, Gustavo Siebra (2024)
The progress of a country is closely tied to the quality of its water, sewage, drainage, and solid waste infrastructure. This study focuses on the Vertente Marítima Basin in Fortaleza, Ceará, a region in the semi-arid Northeast of Brazil that faces water scarcity and natural resource vulnerability. The area has undergone rapid urban expansion, leading to significant challenges for drainage and sewage systems, such as flooding and water pollution. The entry of stormwater into the sewage system, known as illicit inflow, compromises system efficiency, causing overflows and environmental contamination. In light of this, the general objective is to develop a methodology for the simulation and optimization of sewer networks subjected to stormwater and groundwater inflows in urbanized environments. The layout and bathymetry of the East Interceptor (IL) were updated to conduct hydrological-hydraulic modeling, using rainfall data from the Edson Queiroz station, collected between 2018 and 2023. The Rainfall-to-Kinematic Flow (RTK) method was applied to estimate the Rainfall Derived Infiltration and Inflow (RDII), identifying critical system points prone to failure and overload. After validating the scenario with the optimal R value, the Intensity-Duration-Frequency (IDF) equation was applied for different return periods. Results indicated that the Personal Computer Storm Water Management Model (PCSWMM) has a simplified and intuitive interface with integration to QGIS. During model calibration, simulations were performed for 16 days across 2, 4, 8, 10, 25, and 35 sub-basins with varying R values. In the validation phase, 65 days were simulated for two sub-basins, comparing results with data from the Ceará Water and Sewage Company (CAGECE). The best accuracy was achieved with two sub-basins, showing results above 75% for R equal to 0.01. For return periods of 2, 5, and 10 years, the R value of 0.01 maintained the best performance, despite significant increases in water volume. As a network improvement measure, both structural and non-structural solutions are recommended. The model proved adequate for Fortaleza’s reality and can be used as a practical tool for forecasting sewer system overflows. The proposed methodology may also be applicable to other cities with similar characteristics.